The Effect of Accleration and Braking on the Strength of Chopper-Motorcycle Frames under Static Loading Conditions - Gumilar, Aji; Akbar, Rozaqy Nurfadhila (Universitas Insan Cendekia Mandiri, 2025)
Abstract: This study aims to analyze the static strength of two custom chopper motorcycle frame designs considering various loading cases, including normal loading, maximum acceleration, maximum braking, and 5G gravitational acceleration. The analysis is conducted using a numerical simulation approach with the Finite Element Method (FEM) to measure von Mises stress, displacement, and safety factor. The simulation results show significant differences between the two frame designs. Frame 1 exhibits poorer performance with lower safety factors under 5G gravitational acceleration conditions, displaying very high stress and larger displacements, whereas Frame 2 performs better with a consistently safe safety factor across all loading conditions. This study provides important contributions to the development of safer and more functional custom motorcycle frame designs, considering safety aspects in everyday use and modifications.